Students’ Perceptions towards Working in the Tourism and Hospitality Industry in United Arab Emirates - Mannaa, Maryam Taha; Abou-Shouk, Mohamed (Al-Adab Journal, 2020)
There are few studies on student perceptions of working in the tourism sector in Arab and Islamic countries. Taking into account the factors related to the cultural dimensions and to the society, the current study aims to examine the factors that influence the perception of tourism students in United Arab Emirates (UAE) to work in the tourism sector after graduation. Based on a random sample of students enrolled in the tourism program at the university level and using the structural equation modelling technique of analysis, the findings revealed that the commitment of students to work in the tourism sector is negatively influenced by the social aspects, the nature of work and the pay and promotion benefits. The current study is useful for all policy makers in education and tourism businesses to improve the image of tourism jobs in the minds of tourism students in the UAE, as well as to attract and retain skilled national employment and reduce the leakage of tourism income resulting from a high percentage of non-national employment.